No Name, no Fame: A Bibliometric Analysis of Publications of Giftedness in Adults: - Infante Rejano, Eduardo; Scurtu Tura, Maria Claudia; Jiménez Soto, Annabel; Santana, Mónica (ANDULI, Revista Andaluza de Ciencias Sociales, 2023)
We report the first science mapping analysis on adult giftedness field to show its conceptual structure and literature evolution. A bibliometric science mapping tool based on co-word analysis and h-index, through a Science Mapping Analysis Software Tool (SciMAT) was applied. Initially 661 articles published from 1948-2022 were retrieved from the Web of Science (WoS). Refining it by English language and specific descriptors, 376 results were considered, and 28 themes and 32 clusters were identified as significant in giftedness literature using SciMAT software. Data analyses proved that adult giftedness is an emerging study and with a timid development only a decade ago with the support of studies on life-span issues and previous papers on ability. The onset of giftedness in adults seems to come not only from cognitive testing (i.e., intelligence studies) or performance research, but also and more recently from the support of studies focusing on life-satisfaction and qualitative methodologies.